Virtues and Narratives in Medicine: An Analysis and Collection of Virtue-Illustrating Stories in Medical Journals - Lauris C. Kaldjian; Brittany A. Bettendorf; Fabrice Jotterand (Journal of Medical Humanities, 2026)
Abstract This paper draws from a framework of virtue ethics and narrative medicine to present a content analysis and teaching resource of virtue-illustrating stories found in medical journals. As acquired dispositions, virtues are cultivated not merely by listening to lectures but through reflection, experience, role-modeling, practice, and internalization. One way to encourage such cultivation is to use narratives to illustrate moral virtues in action. With this in mind, we identified a literature-based taxonomy of 12 core virtues in medicine, selected a sample of 180 narratives published in medical journals to perform a content analysis and frequency calculation of core virtues they illustrate, and identified a collection of 24 of these narratives to illustrate the 12 core virtues. In decreasing order of frequency, the 12 core virtues found in these narratives were benevolence, humility, practical wisdom, courage, respectfulness, trustworthiness, altruism, cooperativeness, temperance, honesty, integrity, and justice. The taxonomy and bibliographic resource we offer can help medical educators utilize medical narratives to reflect on and discuss core moral virtues in medicine, and the 24 virtue-illustrating narratives are short, accessible, and practical for time-constrained teachers and learners interested in the way stories manifest virtues in medicine. This taxonomical framework and narrative collection can help shine practical light on ethical challenges in medicine—which so often are complex, multilayered, uncertain, and fluid—and on the virtues that enable physicians and other healthcare professionals to respond well to those challenges.